Theoretical design of a new family of two-dimensional topological insulators. Issue 11 (6th March 2017) - Chen, Kai-Xuan; Lyu, Shu-Shen; Luo, Zhi-Yong; Fu, Yuan-Xiang; Heng, Yi; Mo, Dong-Chuan
Abstract : A new family of two-dimensional topological insulators, hydrogenated monolayer of Pb2 XY (X = Ga/In and Y = Sb/Bi), has been predicted in our study. Abstract : A new family of two-dimensional topological insulator, hydrogenated monolayer Pb2 XY (X = Ga/In, Y = Sb/Bi), has been predicted using first-principles density functional theory. The electronic bulk band gap of the proposed systems can be induced in the presence of a spin–orbit coupling effect and its highest value (0.25 eV) was observed in the hydrogenated monolayer Pb2 GaBi, which is suitable for practical application. Our simulation study points out that the nanoribbons derived from this new family harbor gapless edge channels. The non-trivial topological nature was further confirmed by calculating the Z 2 topological invariant. These novel systems provide a new platform for topological phenomena observation and spintronic applications.